Efektifitas Bimbingan Pra Nikah Bagi Calon Pengantin Sebagai Upaya Pendukung Terwujudnya Keluarga Sakinah Mawaddah Warahmah (Studi Kasus pada BP4 KUA Kecamatan Bantar Gebang Kota Bekasi) - Muhammad Iqbal Fauzi; Agus Supriyanto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This study analyzed the implementation of pre-marital guidance at BP4 KUA Bantar GebangDistrict, Bekasi City. This research is descriptive qualitative field research. The method used in thisresearch is sociological juridical. Research Location at the Marriage Preservation and DevelopmentAdvisory Board (BP4) Bantar Gebang District, Bekasi City. Data collection techniques by interview,documentation, and literature study. The results of the study show that the Marriage Guidance andPreservation Agency (BP4) of Bantar Gebang District, Bekasi City has not optimally carried outits role as a supervisor, facilitator, communicator, mediator, and conflict in marriage disputes torealize the BP4 goal of enhancing the quality of marriage to create a sakinah family according to theteachings Islam. Problems faced by clients at BP4 Bantar Gebang Subdistrict, Bekasi City that causedisputes in marriage are infidelity problems, interference from parents or siblings, marriage at a youngage, economic problems, mild-hands husbands, drunken spouses, prostitutes and gamblers, spousesleaving the wife does not come home again, has no children, quarrels, the husband gets a physicaldisability or disease, the way to solve it is BP4 Bantar Gebang District, Bekasi City starting with goodintentions, sincerity, showing empathy, respect, secret Klein, sensitivity seeking root problem solvingas well as guiding and advising clients.